Anxiety Assessment: Psychometric Properties of the Spanish Version of the Burns Anxiety Inventory. (22nd June 2015) - Ortuño-Sierra, Javier; Rodríguez, Lorena; Debbané, Martin; Fonseca-Pedrero, Eduardo
Abstract: The main purpose of this study was to analyze the psychometric properties of the Spanish version of the Burns Anxiety Inventory (Burns-A: Burns, 1993 ). The sample consisted of 417 participants, 387 (29.71% male) healthy participants (control group: M = 35.5 years; SD = 8.40) and 30 (36.66% female) patients (clinical group: M = 35.8 years; SD = 12.94). The internal consistency evaluated through Cronbach' Alpha was 0.95 for the Total Score in both subsamples. The test-retest reliability (two weeks) for Total Score was 0.86 ( F = 13.2, p ≤ .001) for the non-clinical subsample, and 0.95 ( F = 36.5, p ≤ .001) for the clinical subsample. Confirmatory factor analyses supported the initial three-factor model. However, modifications to the initial three-factor model improved the goodness-of-fit indices. Results showed statistically significant differences in the mean scores of the Burns-A between the clinical and control groups. This study supports the Spanish version of the Burns-A as a brief and useful tool for the screening of anxiety symptoms in adult populations. Future studies should investigate measurement invariance across cultures.